OPTIMALISASI PENYEIMBANGAN PROSES PRODUKSI PADA PT. XYZ DENGAN PENDEKATAN LEAN MANUFACTURING DAN METODE VALUE STREAM MAPPING (VSM) - Angga Kusuma Putra; Ari Zaqi Al Faritsy (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The production process at PT.XYZ faces significant challenges related to workload imbalance among production stations and declining raw material quality. This research aims to identify and address bottlenecks using the Lean Manufacturing approach with Value Stream Mapping (VSM), Process Activity Mapping (PAM), idle time analysis, and Fishbone Diagram methods. The main problems include 15% raw material inconsistency and workload imbalance particularly in the cutting department. The research employs a qualitative descriptive approach through direct observation, semi-structured interviews, and documentation analysis. Results demonstrate actual total process time reaching 3,328.48 minutes with only 10.31% value-added (VA) activities. Primary identified waste is the waiting category totaling 2,250 minutes per m³. Through future state mapping implementation, process time is reduced to 1,561.35 minutes and Process Cycle Efficiency (PCE) improves from 52.27% to 53.74%, resulting in 53% overall efficiency increase. This research provides concrete recommendations including strict raw material quality control, cutting department semi-automation, buffer management system implementation, and production schedule adjustment based on line balancing.